2018
DOI: 10.1002/elps.201700397
|View full text |Cite
|
Sign up to set email alerts
|

What is the best ethanol‐water ratio for the extraction of antioxidants from rosemary? Impact of the solvent on yield, composition, and activity of the extracts

Abstract: Extracts rich in antioxidants, such as rosemary extracts, are currently obtained by extraction of the plant material using hydro-alcoholic mixtures with high ethanol content. As this ratio is generally chosen by default and scarcely optimized, we intended to investigate the impact of the hydro-alcoholic composition on extract characteristics such as extraction yield, composition profile in selected compounds, and antioxidant/reducing activity such as Folin-Ciocalteu, DPPH, and ORAC. A theoretical determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 36 publications
3
37
1
Order By: Relevance
“…However, the solubility of the phenolic compounds in the solvent is not the only predominant factor in the extraction of TPC. This could explain why a 100% ethanol ratio is not the best extraction solvent for phenolic, rather, a 50% to 80% ratios yields the best extraction of targeted compounds [24]. This is compatible with the results of the current study, in which a 100% ethanol ratio extraction yielded lower TPC than the 50% ethanol out of all the crude extracts.…”
Section: Tpc Of Md2 Pineapple Peel Crown and Core Extractssupporting
confidence: 90%
“…However, the solubility of the phenolic compounds in the solvent is not the only predominant factor in the extraction of TPC. This could explain why a 100% ethanol ratio is not the best extraction solvent for phenolic, rather, a 50% to 80% ratios yields the best extraction of targeted compounds [24]. This is compatible with the results of the current study, in which a 100% ethanol ratio extraction yielded lower TPC than the 50% ethanol out of all the crude extracts.…”
Section: Tpc Of Md2 Pineapple Peel Crown and Core Extractssupporting
confidence: 90%
“…A study conducted by Filly et al [22] compared the performance of eight alternative solvents (α-pinene, MeTHF, ethyl acetate, ethyl lactate, ethanol, dimethylcarbonate, and water) to n-hexane for extraction of aromas from caraway seeds. The results showed that bio and green solvents have the potential to replace petroleum-based solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Carotenoids are largely used in the food industry as colorants or nutritional ingredients [24]. Several studies have indeed shown the beneficial role of carotenoids in decreasing the risk of diseases [25] such as heart diseases, cardiovascular diseases, and cataracts [22,26,27]. Carrot is considered as an important dietary source of carotenoids, mainly carotenes, which impart their characteristic orange color to carrots.…”
Section: Resultsmentioning
confidence: 99%
“…After the production of rosemary essential oils, the natural phenolic compounds in the residual rosemary have still gained growing interest for direct extraction. Although water or its ethanolic mixture have been recognized as green solvents for extracting rosemary in a sustainable and safe manner, the low extraction yield and unsuitability for the extraction of maximal bioactive compounds other than a single volatile or non-volatile compound limit its application [17,18]. Recently, the application of vegetable oils as alternative solvents for extracting bioactive compounds in various fields has been revisited.…”
Section: Introductionmentioning
confidence: 99%